Endotoxin emissions from commercial composting activities - Deacon, Lewis J.; Pankhurst, Louise J.; Liu, Jian; Drew, Gillian H.; Hayes, Enda T.; Jackson, Simon; Longhurst, James; Longhurst, Philip J.; Pollard, Simon J. T.; Tyrrel, Sean F. (BioMed Central, 2009)
This paper describes an exploratory study of endotoxin emissions and dispersal from a commercial composting facility. Replicated samples of air were taken by filtration at different locations around the facility on 10 occasions. Measurements were made of endotoxin and associated culturable microorganisms. The inflammatory response of cell cultures exposed to extracts from the filters was measured. Endotoxin was detected in elevated concentrations close to composting activities. A secondary peak, of lesser magnitude than the peak at source was detected at 100-150 m downwind of the site boundary. Unexpectedly high concentrations of endotoxin were measured at the most distant downwind sampling point. Extracted endotoxin was found to stimulate human monocytes and a human lung epithelial cell line to produce significant amounts of pro- inflammatory cytokines. On a weight basis, endotoxin extracted from the composting source has a greater inflammatory cytokine inducing effect than commercial E. coli endotoxin.
Keywords: swine confinement buildings exposure assessment health facilities air assessments workers dust